Preliminary report on the paleopathological research of the skeletal material from the Szeged medieval castle excavation - Ősz, Brigitta (Acta Biologica Szegediensis, 2009)
This study introduces some diseases occurred among the medieval population of Szeged. Hitherto 641 individuals have undergone general anthropological investigations. The identification of abnormal bone conditions was mainly performed by gross examination, but in several cases further investigations were required.One of the most common pathological disorders was spinal osteoarthrosis. There were some skeletal evidences of trauma identifiable; particularly fractures of the ribs and upper limbs. The incidence of developmental defects in our skeletal population is moderate. We observed some cases of widespread skeletal hyperostosis (DISH) as well as localized cranial hyperostosis (HFI) and also traces of osteoporotic processes. Porotic hyperostosis, a skeletal symptom of some nutritional deficiencies and also specific diseases, is a common phenomenon in our material.We could notice traces of non-specific infections like isolated periostitis or osteomyelitis and also that of slight bone alterations that can be indicative of early stage tuberculosis. However, the typical angular kyphosis found in one case proves that TB was present in medieval Szeged. Three skeletons showed bone lesions caused possibly by acquired syphilis. In two cases the radiocarbon and archaeological dating suggested precolumbian origin. These treponemal cases complete the list of evidences of pre-Columbian treponematosis in the Old World.